Performance of Targeted Library Preparation Solutions for SARS-CoV-2 Whole Genome Analysis - Klempt, Petr; Brož, Petr; Kašný, Martin; Novotný, Adam; Kvapilová, Kateřina; Kvapil, Petr (Diagnostics, 2020)
Single next-generation sequencing (NGS) proved to be an important tool for monitoring the SARS-CoV-2 outbreak at the global level Until today, thousands of SARS-CoV-2 genome sequences have been published at GISAID (Global Initiative on Sharing All Influenza Data) but only a portion are suitable for reliable variant analysis. Here we report on the comparison of three commercially available NGS library preparation kits. We discuss advantages and limitations from the perspective of required input sample quality and data quality for advanced SARS-CoV-2 genome analysis.